Herdsmen and Farmers Conflict in Nigeria: A Threat to Peace-building and National Security in West Africa - Osimen Goddy Uwa; Edokpa Fadal Mary; Daramola I. Oluwatobi (IJRDO - Journal of Social Science and Humanities Research, 2019)
One of the recurrent security challenges that confront many states in the country is the scourge of Fulani herdsmen. The attacks by the herdsmen on the sedentary communities have being increasing with each passing day. Much has been written on farmers and Fulani herdsmen conflict in Nigeria. The menace posed in the different communities they migrate to for purposes of grazing their cattle is becoming very alarming. They are more and more constituting major security challenges to their host communities. The propensity towards engaging the land and farm owners of the sites they graze their cattle is increasing by the day as they update their arsenal with highly sophisticated weapons. This is the prevalent security challenge in some communities and states in Nigeria. There have been escalations of reported attacks by Fulani herdsmen who brutally kill natives of the invaded farming communities including women and children in various states across the country. Worst affected states include Benue, Nassarawa, Plateau, Taraba, Kaduna, Adamawa, Zamfara, Oyo, Imo, Cross-River and Enugu. There are recurrent clashes of interests between the host farming communities and the nomadic cattle herders. The major causes by our findings revealed that; Destruction of crops by the cattle, Contamination of stream by cattle, disregard for traditional authority, Over-grazing of fallow land, sexual harassment of women by nomads, Harassment of nomads by host youths, Indiscriminate defecation on roads, theft of cattle , stray cattle, and indiscriminate bush burning. The study also observed that there is no resource sustainability in Nigeria hence; it is difficult for the majority of its citizens who require land for farming and grazing to have access to land. And this is one of the major causes of conflict between the parties. The paper therefore, recommended that the problem can be minimized through extension agency intervention to identify stakeholders and development trust between the disputants using the mechanism tagged ―local development plans (LDP) which is community initiated process to reduce tension over access and the use of land and effective participation in decision-making and economic activities in the communities and among others.